Development and Validation of LC-MS/MS Assay for the Quantification of Progesterone in Rat Plasma and its Application to Pharmacokinetic Studies - Sasaki, M.; Ochiai, H.; Takahashi, K.; Suzuki, R.; Minato, K.; Fujikata, A. (Drug Research, 2015)
A sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the determination of progesterone levels in rat plasma. Progesterone-d9 was used as an internal standard (IS). Samples were prepared using salting-out assisted liquid/liquid extraction (SALLE), and the extracts were injected directly onto the LC-MS/MS system. The chromatographic separation was achieved on a CAPCELL PAK C18 MGIII column (100 mm×2.0 mm, i.d. 5 µm) using methanol and aqueous 0.1% formic acid solution gradient as the mobile phase with a constant flow rate of 0.45 mL/min. Electrospray ionization in the positive-ion mode was employed. Multiple reaction monitoring of the precursor to product ion pairs, from m/z 315.20 to m/z 109.10 for progesterone and from m/z 324.26 to m/z 113.07 for the IS, was used for quantification. Good linearity was observed over the concentration range of 0.05–20.00 ng/mL with a weighted (1/x2) linear regression. The intra- and inter-day precision (% relative standard deviation [RSD]) across 3 validation days over the entire concentration range was lower than 6.7%. Accuracy (% nominal) determined at 5 quality control concentrations was between 94.0 and 103.7%. The validation method was applied in a pharmacokinetic study evaluating progesterone levels after intramuscular or vaginal administration to ovariectomized (OVX) rats. The area under the plasma concentration-time curve (AUC) calculated after intramuscular administration was more than 4 times higher than the AUC measured following vaginal administration of a comparable dose.
Keywords: LC-MS/MS; intramuscular administration; vaginal administration; ovariectomized rat; pharmacokinetics; steroids